Provisioning the Posho: Labor Migration and Working-Class Food Systems on the Early-Colonial Kenyan Coast. (2020) - Smart, Devin
Abstract: Engaging questions about social reproduction, migrant labor, and food provisioning, this article examines the emergence of a working-class food system on the coast of Kenya during the early decades of the twentieth century. Like elsewhere in Africa, labor migrants in Kenya's port city of Mombasa and on nearby plantations were provisioned with food rations, which were part of what Patrick Harries calls a "racial paternalism" that structured many labor relations during the colonial period. The article starts in rural Kenya, but then follows labor migrants to their places of employment to examine the formation of this new food system. In upcountry rural societies, women had primarily produced and then exclusively prepared their communities' food. However, as migrants, men received a ration ( posho ) of maize meal or rice as part of their pay, used their cash wages to purchase foodstuffs from nearby markets, and some plantation workers were also able to grow their own vegetables on plots allocated by their employers. After acquiring their food through these wage-labor relations, men then had to cook their meals themselves. In addition the cuisine created by labor migration was one of extreme monotony compared to what these migrants ate in their rural communities, but I also show how food became a point of conflict between management and labor. The article demonstrates how workers successfully pressured their employers to improve the quantity and quality of their rations from the 1910s to the 1920s, while also raising their wages that allowed them to purchase better food. I additionally argue that during this period an "urban" or "rural" context did not fundamentally define how migrant workers acquired their food, as those laboring in both city and countryside received these rations. However, the article concludes by examining how after 1930, economic transformations changed Mombasa's food system so that workers became almost entirely reliant on cash and credit as the way they acquired their daily meals, while paternalism continued to infuse the food systems of rural migrant laborers. In sum, this article is a local study of coastal Kenya that is also concerned with global questions about how food provisioning fits into the social reproduction of working classes in industrial and colonial capitalism.